Qath'iy dan Zhanny dalam Perspektif Pemikiran Islam - Muh Daming K. (Al-'Adl, 2008)
One of the factors of the difference of opinion is the existence of syara 'texts that multi-interpretation, so the theory of qath'iy and zhanny also can not be separated from the problem. This paper attempts to highlight the problem of the theory in the perspective of Islamic legal thought, that there are differences in the way of the ulama ushul scholars, both classical and modern, in applying the two theories. The classical scholars tend to restrict themselves in matters of qath'iy, while modern scholars try to break them